2018
DOI: 10.1101/461590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Focus on the breath: Brain decoding reveals internal states of attention during meditation

Abstract: Evidence suggests meditation may improve health and well-being. However, understanding how meditation practices impact therapeutic outcomes is poorly characterized, in part because existing measures cannot track internal attentional states during meditation. To address this, we applied machine learning to track fMRI brain activity patterns associated with distinct mental states during meditation. Individualized brain patterns were distinguished for different forms of internal attention (breath attention, mind … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(27 citation statements)
references
References 38 publications
5
21
1
Order By: Relevance
“…Focused attention on the body (i.e., meditation) dampens DMPFC activity causing the aINS to attend more fully to the incoming internal stimuli being sent to the pINS from the body leading to a neuroplasticity change in the posterior, mid, and anterior insula (Damasio and Carvalho, 2013; Farb et al, 2013) while simultaneously decoupling the insula from the DMN and DMPFC (Farb et al, 2007, 2013). A more recent study confirmed this finding (Yeng et al, 2018). Yeng et al (2018) found that focused attention on external stimuli and internal sensations yielded distinct neural signatures and participants who were able to focus on their breath (interoceptive stimuli) over a longer period of time were able to dampen self-referential processing and the neural correlates associated with that function, including the mPFC and the DMN.…”
Section: How Mindfulness Modulates the Insulasupporting
confidence: 60%
See 3 more Smart Citations
“…Focused attention on the body (i.e., meditation) dampens DMPFC activity causing the aINS to attend more fully to the incoming internal stimuli being sent to the pINS from the body leading to a neuroplasticity change in the posterior, mid, and anterior insula (Damasio and Carvalho, 2013; Farb et al, 2013) while simultaneously decoupling the insula from the DMN and DMPFC (Farb et al, 2007, 2013). A more recent study confirmed this finding (Yeng et al, 2018). Yeng et al (2018) found that focused attention on external stimuli and internal sensations yielded distinct neural signatures and participants who were able to focus on their breath (interoceptive stimuli) over a longer period of time were able to dampen self-referential processing and the neural correlates associated with that function, including the mPFC and the DMN.…”
Section: How Mindfulness Modulates the Insulasupporting
confidence: 60%
“…A more recent study confirmed this finding (Yeng et al, 2018). Yeng et al (2018) found that focused attention on external stimuli and internal sensations yielded distinct neural signatures and participants who were able to focus on their breath (interoceptive stimuli) over a longer period of time were able to dampen self-referential processing and the neural correlates associated with that function, including the mPFC and the DMN.…”
Section: How Mindfulness Modulates the Insulasupporting
confidence: 60%
See 2 more Smart Citations
“…Zion Health Fund Pilot in Integrative Medicine Research (HW), and Osher Center for Integrative Medicine (OCIM) Jaswa Fund for Meditation Research and Bowes Foundation Research Fund (HW). This manuscript has been released as a pre-print at bioRxiv (Weng et al, 2018 ).…”
mentioning
confidence: 99%